Sport participation in pediatric age affects modifications in diabetes markers in adulthood - Lima, Manoel C. S. [UNESP]; Turi, Bruna C. [UNESP]; Silva, Danilo R. P.; Ritti-Dias, Raphael M.; Cucato, Gabriel G.; Codogno, Jamile S. [UNESP]; Fernandes, Rômulo A [UNESP] (Springer Nature, 2017)
The purpose of this study was to analyze the effect of early sport participation on diabetes markers among adults. This longitudinal study analyzed 107 participants during 12 months of follow-up. Diabetes markers were measured by fasting insulin, fasting glucose, insulin resistance, and glycated hemoglobin. Sports participation during childhood and adolescence was self-reported. Current physical activity was measured by pedometer. Adults with no engagement in sports during early life showed positive relationship between current physical inactivity and higher modification in glucose (β = 1.045 [95%CI 0.267; 1.823]), insulin (β = 0.763 [95%CI 0.121; 1.405]), and insulin resistance (β = 0.295 [95%CI 0.062; 0.529]). Adults engaged in sports during early life had lower values of glucose (p value = 0.029; Eta-squared = 0.049). Glucose levels decreased through the follow-up among adults with early sports participation (p value = 0.005; Eta-squared = 0.074). There was association between lack of early engagement in sports and higher occurrence of altered values during the follow-up for insulin resistance (OR = 8.37 [2.10; 33.3]) and insulin (OR = 7.61 [2.27; 25.4]). Engagement in sport activities during early life affects glycemic variables in adulthood, as well as longitudinal relationship between physical activity in adulthood, and glycemic control also seems affected by early sport participation.
Keywords: Adolescence; Childhood; Glycemic control; Insulin resistance; Physical activity and health